STUDY ON CLEANER PRODUCTION STRATEGY IN THE SMALL SCALE TAPIOCA INDUSTRY: A CASE STUDY IN KELURAHAN CILUAR, NORTH BOGOR SUB-DISTRICT - Anas M. Fauzi, Ainy Rahmawakhida dan Yaoi Hidetoshi (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTSmall scale industries are gaining importance and their contribution to pollution problems cannot be ignored. One of small scale industry having the potential to cause environment problems is centralized of small scale tapioca industries. Small scale industries typically have limited space for the installation of treatment system. In addition, often small scale industries are only marginally profitable, so waste treatment investment may threaten their viability. This problem can be solved by applying cleaner production strategy. This research studies the potentials of cleaner production application and formulating alternatives of cleaner production strategy in order to develop centralized small scale tapioca industry in Ciluar. The cleaner production alternatives which are potential to be applied are good housekeeping, usage of “gobegan”extractor, washing of sedimentation tank daily, water controling, and worker supervision. The investment of these alternatives is Rp 10.052.000 and pay back period (PBP) one year seven manths. Analytical Hierarchy Process (AHP) analysis shows that technology is the most important factor to maximize crude tapioca production efficiency by applying cleaner production. The priority of cleaner production program from AHP analysis is socialization and training of cleaner production application, integrated waste management, and socialization and training of crude tapioca quality increasing procedures.Keywords : cleaner production, small scale industry, tapioca, AHP